Could the multicomponent meningococcal serogroup B vaccine (4CMenB) control Neisseria meningitidis capsular group X outbreaks in Africa? - (:unkn) unknown (My University, 2013)
A new vaccine, 4CMenB, is composed of surface proteins of Neisseria meningitidis and is aimed to target serogroup B (MenB) isolates. The vaccine components are present in meningococcal isolates of other serogroups allowing potential use against meningococcal isolates belonging to non-B serogroups. Isolates of serogroup X (MenX) have been emerged in countries of the African meningitis belt. 4CMenB may offer a vaccine strategy against these isolates as there is no available capsule-based vaccine against MenX. We used the Meningococcal Antigen Typing System (MATS) to determine presence, diversity and levels of expression of 4CMenB antigens among 9 MenX isolates from several African countries in order to estimate the potential coverage of MenX by the 4CMenB vaccine. We performed bactericidal assays against these isolates, using pooled sera from 4CMenB-vaccinated infants, adolescents and adults. The African MenX isolates belonged to the same genotype but showed variation in the vaccine antigens. MATS data and bactericidal assays suggest coverage of the 9 African MenX isolates by 4CMenB but not of two unrelated MenX isolates from France. 4CMenB vaccine can be considered for further investigation to control MenX outbreaks in Africa.
Keywords: African Research